Long‐term functional stability of problem behavior exposed to psychotropic medications. Issue 1 (30th July 2021) - Cox, Alison D.; Virues‐Ortega, Javier
Abstract : Psychopharmacological and behavioral interventions are often combined in the treatment of problem behavior in people with intellectual and developmental disability (IDD). However, little is known about the interaction between medication pharmacodynamics and behavior function. A better understanding of these mechanisms could serve as the conceptual foundation for combined interventions. The current analysis is a systematic replication of Valdovinos et al. (2009). We conducted continuous functional analyses within analogue reversal and parametric analyses monitoring the impact of various dosages of primarily antipsychotic medications on problem behavior and its function. Four individuals with IDD and problem behavior who were also receiving psychotropic medications participated. Medication adjustments produced small to negligible decreases in problem behavior, and behavior function remained largely unchanged through the 14 medication adjustments evaluated. The continuous functional analysis helped to identify what could be delayed medication effects on problem behavior. The clinical and methodological implications of this replication are discussed.